Bioaccumulation of Heavy Metals in Some Selected Benthic Macro-Invertebrates of River Owo, Agbara, Ogun State, Nigeria - Kuforiji, Titilope Shakirat; Ayandiran, Tolulope Akinpelu; Fawole, Olatunde Olubanjo; Balogun, Hassan Adewale; Olanipekun, Abimbola Stephen; Adeyemi, Oluwatosin Olajumoke (European Journal of Applied Sciences, 2024)
Increasing Industrialization, and urbanization, along with the violation of the effluent disposal norms, has caused heavy contamination of water bodies. Macro-invertebrates and other aquatic biota in the vicinity of industrial areas and estates are a good indicated for monitoring the level of pollutions. Heavy metals like cadmium (cd), chromium (cr) have proven to be persistent pollutants. Though present in traces and being lipophilic, heavy metals tend to bioaccumulate and biomagnified. Their accumulation and biotic tissues cause toxic effects. The study was carried out the current levels of total cadmium, chromium, Zinc, copper, Nickel, lead, mercury, and cobalt accumulated in the body of selected macro-invertebrates. Four groups of aquatic macro invertebrates group A; Dragonfly larvae (hagenius sp); group B; crawling water beetle (Elmidae spp.); group C; Freshwater prawn (Parastacidae spp.); group D; Freshwater snail (gastropoda spp.) all were analyzed for their content of these heavy metal. The total Arsenic was ranged from 0.008 to 0.34 (mg/l), cadmium ranges 0.18 to 0.08 (mg/l), lead ranged from 0.019 to 0.72 (mg/l), copper. Ranged from 0.146 to 0.340 (mg/l), chromium ranged from 0.003 to 0.012 (mg/l) of the four samples (A, B, C and D) Concentrations slightly exceeded the prescribes Legal Limits of Lagos state Environmental protection Agency (LASEPA, 2001). The bioaccumulation level of heavy metals investigated in macro-invertebrate shows a little deviation from WHO (2001), FEPA, (1991).